PENGARUH DIMENSI MOTIVASI, KARAKTERISTIK LINGKUNGAN, DAN AKTIVITAS PADA SENSE OF PLACE SHOPPING MALL - Nurul Adha Sitorus; Rahy Rachmawan Sukardi; Karto Wijaya; Hanson Endra Kusuma (Jurnal Arsitektur ARCADE, 2022)
Abstract: The rapid growth of shopping malls in Indonesia creates differences in people's spending motivation. The main purpose of visiting shopping malls is not only for utilitarian activities but for hedonic activities. The difference in shopping motivation is related to the behavior patterns of visitors in carrying out activities. The characteristics of the mall environment play a role in influencing the selection of malls that visitors find attractive. Seeing this phenomenon, this study aims to see the causal relationship between motivation, characteristics of the physical environment, activities, and sense of place experienced by visitors at shopping malls. The research was conducted in two phases, qualitative and quantitative. From the analysis results obtained 7 dimensions of internal motivation, for the category of hedonic motivation (relaxation shopping, role shopping, social shopping, value shopping, adventure shopping), categories of utilitarian motivation (anticipated utility and efficiency shopping), 2 dimensions of physical environment characteristics (green open space). , completeness of facilities), 3 dimensions of activity (group/social, functional and recreational, and entertainment), 3 measurable variables of sense of place (want to visit again, want to linger, feel comfortable). Based on multivariate regression, the results obtained that internal motivation (social shopping) has a strong influence on sense of place, and environmental characteristics do not have a direct influence on sense of place but environmental characteristics encourage a strong influence for someone to carry out certain activities at the shopping mall. and the activities carried out also affect the sense of place in the shopping mall.Abstrak: Pesatnya pertumbuhan shopping mall saat ini, menyebabkan perbedaan motivasi berbelanja dalam mengunjungi mall. Tujuan utama mengunjungi mall bukan hanya melakukan aktivitas utilitarian tetapi juga aktivitas hedonik. Perbedaan ini berkaitan dengan pola perilaku pengunjung dalam melakukan aktivitas. Karakteristik lingkungan mall berperan dalam mempengaruhi pemilihan mall yang menurut pengunjung menarik. Melihat fenomena tersebut, adapun penelitian ini berusaha untuk melihat hubungan sebab akibat antara motivasi, karakteristik lingkungan fisik, aktivitas, dan sense of place yang dialami pengunjung saat di shopping mall. Penelitian dilakukan dalam dua fase, kualitatif dan kuantitatif. Dari hasil analisis diperoleh 7 dimensi motivasi internal, untuk kategori motivasi hedonik (relaxation shopping, role shopping, social shopping, value shopping, adventure shopping), kategori motivasi utilitarian (anticipated utility dan efficency shopping ), 2 dimensi karakteristik lingkungan fisik ( ruang terbuka hijau, kelengkapan fasilitas), 3 dimensi aktivitas (berkelompok/sosial, fungsional dan rekreasional, dan hiburan), 3 variabel terukur sense of place (ingin berkunjung kembali, ingin berlama-lama, merasa nyaman). Berdasarkan regresi multivariat, diperoleh hasil motivasi internal (social shopping) memiliki pengaruh yang kuat terhadap sense of place, dan karakteristik lingkungan tidak memiliki pengaruh secara langsung terhadap sense of place namun karakteristik lingkungan mendorong pengaruh yang kuat bagi seseorang untuk melakukan kegiatan tertentu di shopping mall, dan kegiatan yang dilakukan tersebut juga mempengaruhi sense of place di shopping mall